A lutetium / cerium yellow-green phosphor for white LEDs and its preparation method

By using turpter/cerium yellow-green phosphor and two-step precipitation method in LED phosphor, the problem of thermal quenching of LED phosphor at high temperature is solved, and the phosphor with high thermal stability and luminous intensity is achieved, reducing the cost and It has band adjustability.

CN118496857BActive Publication Date: 2025-02-14JIANGMEN KANHOO IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410380837.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-31
Publication Date
2025-02-14
Estimated Expiration
2044-03-31

AI Technical Summary

Technical Problem

Existing LED phosphors have thermal quenching problems at high temperatures, resulting in spectral movement and luminous intensity drops, affecting the light efficiency and life of white LEDs.

Method used

Using lete/cerium yellow-green phosphor, cerium and letetium oxide were precipitated on the substrate surface by two-step precipitation method, and Ce3+ was migrated to the core surface through the precipitation process to form fluorescence with the chemical formula (CexLuyY(3-x-y-z)Mz)Al5O12. pink.

Benefits of technology

It improves the thermal stability and luminous intensity of the phosphor, reduces the use of rare earth gluten, reduces the cost, and achieves adjustable band yellow-green fluorescence.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004768812480000101
    Figure BDA0004768812480000101
  • Figure BDA0004768812480000111
    Figure BDA0004768812480000111
Patent Text Reader

Abstract

The present application belongs to the technical field of fluorescent material preparation, and discloses a lutetium / cerium yellow-green phosphor for white light LED, wherein the lutetium / cerium yellow-green phosphor for white light LED comprises a matrix and cerium-containing oxide and lutetium-containing oxide shallowly doped on the surface of the matrix, wherein the shallow doping is achieved by the migration of the cerium-containing oxide and lutetium-containing oxide precipitated on the surface of the matrix into the interior of the matrix; the chemical formula of the lutetium / cerium yellow-green phosphor for white light LED is (Ce x Lu y Y (3‑x‑y‑z) M z )Al5O 12 ; Wherein, M is selected from at least one of the elements Li, Na, Mg, K, Ca, and Sc, and 0.03≤x≤0.06, 1.00≤y≤2.00, and 0.05≤z≤0.1. The present application obtains a phosphor with good thermal stability and high luminous intensity through the above design. In addition, the present application also discloses a method for preparing the above-mentioned lutetium / cerium yellow-green phosphor for white light LEDs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fluorescent material preparation, and in particular to a lutetium / cerium yellow-green fluorescent powder for white light LED and a preparation method thereof. Background Art

[0002] White light LED is called the fourth generation lighting source or green light source. It has the advantages of high efficiency and energy saving, green environmental protection, long life and good reliability. LED is widely used in commercial lighting, home lighting, classroom lighting, signal indication, automotive lighting, backlight source of liquid crystal display and other fields. The light emission mode of LED is a combination of LED phosphor and GaN blue light chip. After absorbing the blue light emitted by the GaN chip, the LED phosphor emits yellow light, green light or red light of different bands, which is mixed with the blue light partially transmitted by the GaN chip to realize white light. In LED lighting, as the temperature rises, the luminous intensity of the blue light GaN chip and LED phosphor will decrease, especially the LED phosphor will have spectral shift and the luminous intensity will decrease significantly. The temperature quenching of LED phosphor caused by heating will seriously affect the light efficiency, colorimetric performance and life of white light LED.

[0003] Projection display, automotive lighting, medical lighting, automotive lighting, ultra-long-distance lighting, laser scanning and other high-power and laser lighting fields require LED phosphors with good thermal stability and low thermal quenching. At present, conventional YAG, GaYAG or silicate green powder and yellow powder on the market are used in high-power and laser lighting fields, and have obvious thermal quenching and poor high temperature resistance. Under high-power laser irradiation, GaYAG or silicate green powder and yellow powder melt and blacken, resulting in obvious light decay. The heat resistance of YAG phosphor is slightly better than that of GaYAG or silicate green powder and yellow powder, but the brightness is low and the wavelength is 550nm-570nm, the wavelength is long, and the green light spectrum is missing. The color rendering index after packaging is lower than 80.

[0004] In his dissertation "Preparation and Performance Study of Cerium-doped Yttrium / Lutetium Aluminum Garnet Fluorescent Materials", Xu Jian from Xiamen University recorded several preparation methods for cerium-doped Yttrium / Lutetium Aluminum Garnet phosphors, including high-temperature solid-phase method, precipitation method, sol-gel method, spray pyrolysis method, hydrothermal method, etc. Among them, "the high-temperature solid-phase method is to mix the solid raw material powders evenly according to a certain stoichiometric ratio, and then place them in a furnace for heat treatment to obtain the target product through solid-phase reaction. The high-temperature solid-phase method is also the most important method for industrial production. However, the literature records that the high-temperature solid-phase method has the disadvantages of high energy, relatively low phase purity, and difficult to control particle size."

[0005] The precipitation method is divided into two types: co-precipitation and heterogeneous precipitation. The document states that "when preparing LuAG:Ce phosphor by co-precipitation, ammonium bicarbonate is used as a precipitant to 3+, m 3+ and Ce 3+ The precipitation is carried out with hydroxide to achieve molecular or nano-scale mixing. Then, the nano-scale LuAG:Ce phosphor is obtained through high-temperature heat treatment. ", and the document records that the precipitation method has the advantages of low synthesis temperature and low energy consumption, and the raw materials are mixed evenly and the phase purity is high compared to the solid phase method.

[0006] The sol-gel method generally obtains the target powder through the processes of hydrolysis, polycondensation, peptization, gelation, aging, drying and heat treatment between solutions of inorganic salts, metal alkoxides, etc.

[0007] Regarding the application of spray pyrolysis, the document states that "the preparation of phosphors by spray method has not been actually industrialized", and analyzes that the reason may be caused by problems such as high comprehensive cost and high process difficulty; at the same time, the document states that the hydrothermal method often cannot obtain well-crystallized crystals in one go, and further heat treatment is required to overcome the above shortcomings.

[0008] Chinese patent application 201510120629.4 discloses a method for preparing a rare earth luminescent material containing a crystal defect repair process and its product, wherein the preparation method includes four steps: preparing clinker, preparing clinker doped with raw material, preparing phosphor material after secondary annealing, and obtaining a finished product of the fluorescent material. The product obtained by the preparation method of the present invention has an external quantum efficiency of 0.706 to 0.745 and an internal quantum efficiency of 0.953 to 0.992 within a temperature range of room temperature to 150°C; the scheme replaces the activator with raw material during secondary reduction, and thereby eliminates crystal defects and improves Ce through the combined action of surface modification and secondary reduction thermodynamics. 3+ Internal quantum efficiency and thermal stability of luminescence from garnet-structured rare earth aluminate luminescent materials."

[0009] Further observing the scheme, the specific preparation method is: "Step 1: uniformly mix the flux, the fluorescent material matrix material used for primary sintering and the cerium-containing activator, and calcine in a reducing atmosphere; after the calcined product is taken out of the furnace, it is crushed, washed with water and dried in sequence to obtain a clinker;

[0010] The fluorescent material matrix used for primary sintering is a mixed powder of rare earth luminescent element oxide and aluminum oxide, wherein the chemical formula of the rare earth luminescent element oxide is RE2O3, wherein RE is one or more of yttrium, terbium, gadolinium, scandium or lutetium, and O in the chemical formula is oxygen;

[0011] The cerium-containing activator is cerium oxide, cerium trioxide or cerium nitrate;

[0012] The molar ratio of rare earth luminescent element oxide, aluminum oxide and cerium-containing activator is 3-2X:5:2X, wherein X is in the range of 0.05 to 0.07; the calcination temperature in step 1 is in the range of 1300 to 1500°C;

[0013] Step 2: adding raw material to the clinker obtained in step 1, and uniformly mixing the clinker and the raw material by dry method to obtain clinker mixed with raw material;

[0014] The raw material is a fluorescent matrix material used for secondary repair or a calcined oxalate precipitate;

[0015] The dry method refers to not adding organic solvents and inorganic solvents during the mixing process;

[0016] Step 3: subjecting the clinker mixed with raw materials obtained in step 2 to secondary annealing reduction in a reducing atmosphere to obtain a phosphor material that has undergone secondary annealing; the annealing reduction temperature in step 2 is between 800 and 1200° C. or between 1300 and 1500° C.;

[0017] Step 4: Screening and grading the secondary annealed fluorescent powder obtained in step 3 to obtain a finished fluorescent material;”

[0018] At the same time, the scheme states in the specification that "after repeated experiments and research, the use of Gd with a larger ion radius 3+ or Tb 3+ Replace Y 3+ , or use Gd 3+ , Tb 3+ , Y 3+ Replace Lu 3+ , or use Gd 3+ , Tb 3+ , Y 3+ 、Lu 3+ Replace Sc 3+ , which can better remove the Ce on the surface of the phosphor particles after the first sintering. 3+ Squeeze into RE3Al5O 12 Lattice lattice, repair surface defects and improve luminous efficiency"

[0019] It can be seen that the addition of rare earth luminescent elements in this scheme can repair surface defects and improve luminescence efficiency to a certain extent.

[0020] The above scheme adopts a high temperature solid phase method to prepare a fluorescent material with low number of surface defects and high luminous efficiency.

[0021] The problem that this solution needs to solve is: how to provide a phosphor material with a more advantageous structure to improve its luminous efficiency. Summary of the invention

[0022] One of the purposes of this application is to provide a phosphor material with a more advantageous structure to improve its luminous efficiency;

[0023] Another object of the present application is to provide a preparation method, by which the above-mentioned phosphor material with a more advantageous structure is prepared.

[0024] To achieve the above-mentioned purpose, the present application discloses a lutetium / cerium yellow-green phosphor for white light LEDs, the lutetium / cerium yellow-green phosphor for white light LEDs comprising a matrix and cerium-containing oxide and lutetium-containing oxide shallowly doped on the surface of the matrix, wherein the shallow doping is achieved by the migration of the cerium-containing oxide and lutetium-containing oxide precipitated on the surface of the matrix into the interior of the matrix;

[0025] The chemical formula of the lutetium / cerium yellow-green phosphor for white light LED is (Ce x Lu y Y (3-x-y-z) M z )Al5O 12 ;

[0026] Wherein, M is selected from at least one of Li, Na, Mg, K, Ca, and Sc elements, and 0.03≤x≤0.06, 1.00≤y≤2.00, and 0.05≤z≤0.1.

[0027] Preferably, 0.042≤x≤0.048, 1.30≤y≤1.50, and 0.06≤z≤0.08.

[0028] Preferably, the dominant wavelength of the lutetium / cerium yellow-green phosphor for white light LED is 560-570 nm, the peak wavelength is 530-540 nm, and the half-wave width is 100-110 nm.

[0029] Preferably, the brightness of the lutetium / cerium yellow-green phosphor for white light LED is not less than 103%.

[0030] In addition, the present application also discloses a method for preparing the above-mentioned lutetium / cerium yellow-green phosphor for white light LED, comprising the following steps:

[0031] Step 1: dissolving, mixing and precipitating yttrium salt, salt containing M element and aluminum salt to obtain a matrix;

[0032] Step 2: dissolving and mixing the cerium salt and the lutetium salt to obtain an intermediate solution 2;

[0033] Step 3: Place the substrate prepared in step 1 in the intermediate solution 2 for heating and precipitation to obtain lutetium / cerium yellow-green phosphor for white light LED.

[0034] Preferably, the yttrium salt is selected from any one of a chloride salt containing yttrium, a nitrate containing yttrium, a sulfate containing yttrium, and a carbonate containing yttrium;

[0035] The salt containing element M is selected from any one of chloride salt containing element M, nitrate containing element M, sulfate containing element M, and carbonate containing element M;

[0036] The aluminum salt is selected from any one of a chloride salt containing aluminum, a nitrate containing aluminum, a sulfate containing aluminum, and a carbonate containing aluminum;

[0037] The cerium salt is selected from any one of a chloride salt containing cerium, a nitrate containing cerium, a sulfate containing cerium, and a carbonate containing cerium;

[0038] The lutetium salt is selected from any one of chloride salts containing lutetium, nitrates containing lutetium, sulfates containing lutetium, and carbonates containing lutetium.

[0039] Preferably, step 1 comprises the following sub-steps:

[0040] Step A1: dissolving and mixing yttrium salt, salt containing element M and aluminum salt to obtain an intermediate solution 1;

[0041] Step A2: adding the first alkaline precipitation solution to the intermediate solution 1 until the pH value reaches 9-10 to obtain a matrix;

[0042] The first alkaline precipitating liquid is selected from at least one of ammonium bicarbonate and ammonium carbonate.

[0043] Preferably, step 3 includes the following sub-steps:

[0044] Step B1: mixing the matrix prepared in step 1 with the intermediate solution 2 prepared in step 2, heating in a water bath, stirring, adding a second alkaline precipitation solution until the pH value is 9 to 10, and separating the solid and the liquid to obtain a precipitate;

[0045] Step B2: mixing the precipitate with a surfactant, heating, drying, sieving, burning, crushing, ball milling, and sieving to obtain lutetium / cerium yellow-green phosphor for white light LED;

[0046] The second alkaline precipitating liquid is selected from at least one of ammonium bicarbonate and ammonium carbonate;

[0047] The surfactant is selected from at least one of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, and polyoxyethylene fatty acid ester;

[0048] The mass ratio of the surfactant to the precipitate is 0.5 to 5:100.

[0049] Preferably, in step B1, the water bath heating temperature is 40-90° C., and the dropping rate of the alkaline precipitating solution is 50-200 ml / min.

[0050] Preferably, step B2 specifically includes:

[0051] The precipitate is mixed with a surfactant and emulsified at 90-110° C. for 2 hours, then dried and sieved to obtain a powder. The powder and a flux are mixed, ground and placed in a crucible, and then heated at 1400-1600° C. for 4-8 hours. After cooling, the powder is crushed, ball-milled and sieved to obtain lutetium / cerium yellow-green phosphor for white light LEDs.

[0052] The beneficial effects of this application are:

[0053] The lutetium used in the present application is a heavy atomic element, and the raw material is expensive. It is precipitated on the surface of the core by a two-step precipitation method, which can reduce the use of rare earth lutetium to achieve the effect of reducing costs. After reducing the use of rare earth lutetium, the fluorescent material can still obtain good luminescence intensity. In addition, during the precipitation process, the rare earth lutetium continuously migrates to the core and occupies the rare earth yttrium vacancy and replaces the position of yttrium in the lattice, thereby weakening the temperature quenching effect caused by the vibration of the matrix lattice at high temperature, achieving good thermal stability, high luminescence intensity and narrow half-wave width. 3+ The ionic radius is slightly smaller than Y 3+ Yes, with Lu 3+ Increase, the emission wavelength of the yellow-green phosphor gradually decreases to achieve adjustable band;

[0054] On the other hand, Ce deposited on the surface of the core 3+ After burning and reduction, the valence state will change, and the absorption of energy will realize df orbital transition and cause luminescence. 3+ It precipitates on the surface of the core, improves the utilization rate of the Ce element, reduces the concentration of the Ce element, avoids concentration quenching, and improves the luminescence efficiency. DETAILED DESCRIPTION

[0055] The present application will be described clearly and completely below in conjunction with the examples of the present application. In the description of the present application, it should be noted that if the specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0056] Example 1

[0057] Step 1:

[0058] Step A1: Prepare YCl3 solution, LiCl solution and Al2(NO3)3 solution in a molar ratio of Y:Li:Al=1.602:0.06:5, then pour the above solution into a beaker and stir for 10 minutes to obtain intermediate solution 1;

[0059] Step A2: Rapidly add NH4HCO3 solution to the intermediate solution 1 within 1 minute until the pH value is 9-10 to obtain a matrix;

[0060] Step 2: Prepare CeCl3 solution and Lu2(NO3)3 according to the molar ratio of Ce:Lu:Y=0.038:1.3:1.602 and pour the above solution into a beaker and stir for 10 minutes to obtain intermediate solution 2;

[0061] Step 3:

[0062] Step B1: Add the substrate and the intermediate solution 2 into a beaker, and then place it in a water bath reactor, set the water bath temperature to 70°C, turn on the stirrer, stir the substrate and the intermediate solution 2 for 10 minutes, then add NH4HCO3 solution to the beaker at a drop rate of 100 ml / min until the pH value is 9-10, and then stir for 60 minutes. After the stirring is completed, age the precipitate for 24 hours, and then use a Buchner funnel for solid-liquid separation to obtain a precipitate;

[0063] Step B2: adding the precipitate into an autoclave, adding a surfactant, cetyltrimethylammonium bromide, to the precipitate, heating to 100° C. for emulsification and dispersion for 2 hours, then loading into a tray, drying at 120° C. for 12 hours, naturally cooling and passing through a 160-mesh sieve to obtain a dried precipitate;

[0064] The dried precipitate was placed in an alumina crucible, placed in a muffle furnace, set at 900°C, and kept warm for 4 hours; after the powder cooled, it was passed through a roller, sieved, etc. to obtain the calcined precursor; 100g of the calcined precursor was weighed into an agate mortar, and then 0.5g of ammonium chloride was added. After fully grinding, it was placed in an alumina crucible and reduced in a reducing atmosphere at a reduction temperature of 1500°C for 6 hours. After the powder cooled naturally, it was crushed, ball-milled, sieved, washed, dried, and other post-processing was performed to obtain a chemical formula of (Ce 0.038 Lu 1.3 Y 1.602 Li 0.06 )Al5O 12 Lutetium / cerium yellow-green phosphor for white light LEDs.

[0065] Example 2

[0066] Basically the same as Example 1, except that the molar ratio of Y:Li:Ce:Lu is 0.87:0.1:0.03:2.

[0067] Example 3

[0068] It is basically the same as Example 1, except that the molar ratio of Y:Li:Ce:Lu is 1.89:0.05:0.06:1.

[0069] Example 4

[0070] Basically the same as Example 1, except that the molar ratio of Y:Li:Ce:Lu is 1.398:0.06:0.042:1.50.

[0071] Example 5

[0072] Basically the same as Example 1, except that the molar ratio of Y:Li:Ce:Lu is 1.572:0.08:0.048:1.30.

[0073] Example 6

[0074] The method is substantially the same as Example 1, except that the same molar amount of KCl is used instead of LiCl.

[0075] Example 7

[0076] The method is substantially the same as Example 1, except that the same molar amount of ScCl3 is used instead of LiCl.

[0077] Example 8

[0078] It is basically the same as Example 1, except that KCl and ScCl3 are used instead of LiCl, and the total molar amount of KCl and ScCl3 is the same as that of LiCl, wherein the molar ratio of KCl to ScCl3 is 1:1.

[0079] Example 9

[0080] The method is substantially the same as Example 1, except that octadecyltrimethylammonium chloride is used instead of hexadecyltrimethylammonium bromide.

[0081] Example 10

[0082] The method is substantially the same as Example 1, except that polyoxyethylene fatty acid ester is used instead of hexadecyltrimethylammonium bromide.

[0083] Embodiment 11

[0084] The method is substantially the same as Example 1, except that a mixture of cetyltrimethylammonium bromide and polyoxyethylene fatty acid ester is used instead of cetyltrimethylammonium bromide, and the mass ratio of cetyltrimethylammonium bromide to polyoxyethylene fatty acid ester is 1:1.

[0085] Example 12

[0086] The method is substantially the same as Example 8, except that a mixture of cetyltrimethylammonium bromide and polyoxyethylene fatty acid ester is used instead of cetyltrimethylammonium bromide, and the mass ratio of cetyltrimethylammonium bromide to polyoxyethylene fatty acid ester is 1:1.

[0087] Comparative Example 1

[0088] The method is basically the same as Example 1, except that the CeCl3 solution in step 2 is added to step A1 to obtain an intermediate solution containing cerium ions.

[0089] Comparative Example 2

[0090] It is basically the same as Example 1, except that the Lu2(NO3)3 solution in step 2 is added to step A1 to obtain an intermediate solution containing lutetium ions.

[0091] Comparative Example 3

[0092] It is basically the same as Example 1, except that the CeCl3 solution and Lu2(NO3)3 solution in step 2 are added to step A1 to obtain an intermediate solution 1 containing cerium ions and lutetium ions.

[0093] Comparative Example 4

[0094] Basically the same as Example 1, except that the molar ratio of Y:Li:Ce:Lu is 0.89:0.01:0.1:2.0.

[0095] Comparative Example 5

[0096] Basically the same as Example 1, except that the molar ratio of Y:Li:Ce:Lu is 1.99:0.2:0.01:0.8.

[0097] Comparative Example 6

[0098] The method is substantially the same as Example 1, except that sodium dodecyl sulfate is used instead of hexadecyltrimethylammonium bromide.

[0099] Comparative Example 7

[0100] The method is substantially the same as Example 1, except that sodium lauryl ether sulfate is used instead of hexadecyl trimethyl ammonium bromide.

[0101] Performance Test:

[0102] GB / T23595.2-2009 "Test Method for Rare Earth Yellow Phosphor for White Light LED Lamps: Part 2: Determination of Relative Brightness": Use 460nm quasi-monochromatic light as the excitation light source to excite the rare earth yellow phosphor for white light LED lamps (referred to as yellow powder). After the generated fluorescence is collected, the light signal is converted into an electrical signal through a photodetector calibrated by the V(λ) function. Test the photocurrent values ​​of the standard powder and the sample to be tested under the same conditions, and read the relative brightness value of the sample to be tested with the photocurrent value of the standard powder as 100.

[0103] Among them, the national standard sample number of standard powder is GSB 04-3888-2021;

[0104] The dominant wavelength, peak wavelength and half-wave width of the phosphor are tested by fluorescence spectrometer;

[0105] At the same time, the particle size of the phosphor was tested, and the results are shown in Table 1:

[0106] Table 1

[0107]

[0108]

[0109] Result analysis:

[0110] 1. It can be seen from Examples 1-5 that when 0.042≤x≤0.048, 1.30≤y≤1.50, and 0.06≤z≤0.08, Examples 4-5 have significantly higher brightness (luminous intensity) than Examples 1-3. Therefore, when the luminous intensity of the phosphor is required to be higher, we recommend that 0.042≤x≤0.048, 1.30≤y≤1.50, and 0.06≤z≤0.08 be set. At the same time, we can see that the difference between D90 and D10 of the particle size of Examples 4-5 is significantly smaller than that of Examples 1-3. Therefore, the uniformity of the particle size of the phosphor under this ratio is also improved to a certain extent;

[0111] 2. It can be seen from Examples 6-8 that when KCl and ScCl3 are co-doped, the brightness of the phosphor is further improved. At the same time, it can be seen from Examples 6-7 that when other elements such as K and Sc are used to replace Li, the brightness of the phosphor does not change significantly;

[0112] 3. It can be seen from Examples 9-12 that when the mixture of hexadecyltrimethylammonium bromide and polyoxyethylene fatty acid ester is compounded and used, the luminescence brightness of the phosphor is further improved. We speculate that the reason for this phenomenon is that with the use of surfactants, the crystal form of the phosphor is fuller and the particle concentration is high, thereby enhancing the thermal stability and brightness of the phosphor;

[0113] 4. It can be seen from Example 1 and Comparative Examples 1-2 that in Comparative Examples 1-2, Ce and Lu are mixed with yttrium salt, aluminum salt and lithium salt in step 1 to prepare intermediate solution 1. Although Comparative Examples 1 and 2 are also doped with Ce and Lu, compared with Example 1, the cerium and lutetium near the surface of the phosphor are reduced, which leads to an increase in yttrium pores on the surface of the phosphor and an increase in the temperature quenching effect caused by the vibration of the lattice at high temperature, which leads to a decrease in the brightness of the phosphor;

[0114] 5. It can be seen from 6-7 that when anionic surfactants are used instead of cationic surfactants, the brightness of the phosphor will show a certain downward trend. We believe that in the scheme, anionic surfactants cannot achieve good dispersion ability.

[0115] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A lutetium / cerium yellow-green phosphor for white light LED, characterized in that: The lutetium / cerium yellow-green phosphor for white light LED comprises a matrix and cerium-containing oxide and lutetium-containing oxide shallowly doped on the surface of the matrix, wherein the shallow doping is achieved by the migration of the cerium-containing oxide and lutetium-containing oxide precipitated on the surface of the matrix into the interior of the matrix; The chemical formula of the lutetium / cerium yellow-green phosphor for white light LED is (Ce x Lu y Y (3-x-y-z) M z )Al5O 12 ; Wherein, M is selected from at least one of Li, Na, Mg, K, Ca, and Sc elements, and 0.03≤x≤0.06, 1.00≤y≤2.00, and 0.05≤z≤0.1; The method for preparing the lutetium / cerium yellow-green phosphor for white light LED is characterized by comprising the following steps: Step 1: dissolving, mixing and precipitating yttrium salt, salt containing M element and aluminum salt to obtain a matrix; Step 2: dissolving and mixing the cerium salt and the lutetium salt to obtain an intermediate solution 2; Step 3: placing the substrate obtained in step 1 in the intermediate solution 2 for heating and precipitation to obtain lutetium / cerium yellow-green phosphor for white light LED; The step 3 includes the following sub-steps: Step B1: mixing the matrix prepared in step 1 with the intermediate solution 2 prepared in step 2, heating in a water bath, stirring, adding a second alkaline precipitation solution until the pH value is 9 to 10, and separating the solid and the liquid to obtain a precipitate; Step B2: mixing the precipitate with a surfactant, heating, drying, sieving, burning, crushing, ball milling, and sieving to obtain lutetium / cerium yellow-green phosphor for white light LED; The second alkaline precipitating liquid is selected from at least one of ammonium bicarbonate and ammonium carbonate; The surfactant is selected from at least one of cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride, and polyoxyethylene fatty acid ester; The mass ratio of the surfactant to the precipitate is 0.5 to 5:100; Step B2 is specifically as follows: The precipitate is mixed with a surfactant and emulsified at 90-110° C. for 2 hours, then dried and sieved to obtain a powder. The powder and a flux are mixed, ground and placed in a crucible, and then heated at 1400-1600° C. for 4-8 hours. After cooling, the powder is crushed, ball-milled and sieved to obtain lutetium / cerium yellow-green phosphor for white light LEDs.

2. The lutetium / cerium yellow-green phosphor for white light LED according to claim 1, characterized in that: 0.042≤x≤0.048, 1.30≤y≤1.50, 0.06≤z≤0.

08.

3. The lutetium / cerium yellow-green phosphor for white light LED according to claim 1, characterized in that: The main wavelength of the lutetium / cerium yellow-green phosphor for white light LED is 560-570nm, the peak wavelength is 530-540nm, and the half-wave width is 100-110nm.

4. The lutetium / cerium yellow-green phosphor for white light LED according to claim 1, characterized in that: The brightness of the lutetium / cerium yellow-green phosphor for white light LED is not less than 103%.

5. A method for preparing the lutetium / cerium yellow-green phosphor for white light LED according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: dissolving, mixing and precipitating yttrium salt, salt containing M element and aluminum salt to obtain a matrix; Step 2: dissolving and mixing the cerium salt and the lutetium salt to obtain an intermediate solution 2; Step 3: placing the substrate obtained in step 1 in the intermediate solution 2 for heating and precipitation to obtain lutetium / cerium yellow-green phosphor for white light LED; The step 3 includes the following sub-steps: Step B1: mixing the matrix prepared in step 1 with the intermediate solution 2 prepared in step 2, heating in a water bath, stirring, adding a second alkaline precipitation solution until the pH value is 9 to 10, and separating the solid and the liquid to obtain a precipitate; Step B2: mixing the precipitate with a surfactant, heating, drying, sieving, burning, crushing, ball milling, and sieving to obtain lutetium / cerium yellow-green phosphor for white light LED; The second alkaline precipitating liquid is selected from at least one of ammonium bicarbonate and ammonium carbonate; The surfactant is selected from at least one of cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride, and polyoxyethylene fatty acid ester; The mass ratio of the surfactant to the precipitate is 0.5 to 5:100; Step B2 is specifically as follows: The precipitate is mixed with a surfactant and emulsified at 90-110° C. for 2 hours, then dried and sieved to obtain a powder. The powder and a flux are mixed, ground and placed in a crucible, and then heated at 1400-1600° C. for 4-8 hours. After cooling, the powder is crushed, ball-milled and sieved to obtain lutetium / cerium yellow-green phosphor for white light LEDs.

6. The method for preparing the lutetium / cerium yellow-green phosphor for white light LED according to claim 5, characterized in that: The yttrium salt is selected from any one of a chloride salt containing yttrium, a nitrate containing yttrium, a sulfate containing yttrium, and a carbonate containing yttrium; The salt containing element M is selected from any one of chloride salt containing element M, nitrate containing element M, sulfate containing element M, and carbonate containing element M; The aluminum salt is selected from any one of a chloride salt containing aluminum, a nitrate containing aluminum, a sulfate containing aluminum, and a carbonate containing aluminum; The cerium salt is selected from any one of a chloride salt containing cerium, a nitrate containing cerium, a sulfate containing cerium, and a carbonate containing cerium; The lutetium salt is selected from any one of chloride salts containing lutetium, nitrates containing lutetium, sulfates containing lutetium, and carbonates containing lutetium.

7. The method for preparing the lutetium / cerium yellow-green phosphor for white light LED according to claim 5, characterized in that: The step 1 comprises the following sub-steps: Step A1: dissolving and mixing yttrium salt, salt containing element M and aluminum salt to obtain an intermediate solution 1; Step A2: adding the first alkaline precipitation solution to the intermediate solution 1 until the pH value reaches 9-10 to obtain a matrix; The first alkaline precipitating liquid is selected from at least one of ammonium bicarbonate and ammonium carbonate.

8. The method for preparing the lutetium / cerium yellow-green phosphor for white light LED according to claim 5, characterized in that: In step B1, the water bath heating temperature is 40-90° C., and the dropping rate of the alkaline precipitating solution is 50-200 ml / min.

Citation Information

Patent Citations

  • Preparation method and product of rare earth luminescent material containing crystal defect repairing process

    CN104818023B

  • Aluminate green fluorescent powder with core-shell structure and preparation method thereof

    CN102373060A

  • Method for manufacturing ce-doped YAG light-emitting ceramic

    WO2018024014A1